Identification of Near-Isogenic Lines Resistance to Rice Yellow Mottle Virus - Jaw, A.; Ndjionndjop, M.N.; Akromah, R.; Séré, Y. (2012)
Rice yellow mottle virus (RYMV) is a serious disease in rice production in the lowland and irrigated ecologies. Astudy was conducted to examine the resistance of rice (Oryza sp.) lines RYMV. One hundred near-isogenic lines(NILs) from BC2F7 population derived from cross combination: Gigante (Oryza indica cv.) x IR64, Gigante xFK28 and Gigante x IR47 were evaluated. Twenty NILs were identified to be resistant to RYMV BF27 isolatefrom phenotypic screening. Enzyme-Linked-immunosorbent assay (ELISA) test revealed 36 lines to be resistantto RYMV with low virus content. Foreground selection using the gene marker, revealed 22 lines showed introgressionof rymv1-2 allele. On the average, 71% of the markers used in the evaluation showed polymorphism. The highestproportion of recurrent parental contribution was obtained from the cross Gigante x IR64; and the lowest fromGigante x IR47. Individuals from Gigante x FK28 had the highest percentage of the donor parent (70%) andGigante x IR64 had the lowest value but showed the highest genomic proportion of the recurrent parent (57%)was showed by Gigante x IR64